Loss of Hsp90 Association Up-Regulates Src-Dependent ErbB2 Activity - Xu, Wanping (American Society for Microbiology, 2007)
The receptor tyrosine kinase ErbB2 plays a crucial role in tumorigenesis. We showed previously that the molecular chaperone Hsp90 protects ErbB2 from proteasome-mediated degradation by binding to a short loop structure in the N-lobe of the kinase domain. Here we show that loss of Hsp90 binding correlates with enhanced ErbB2 kinase activity and its transactivating potential, concomitant with constitutively increased phosphorylation of Tyr877, located in the activation loop of the kinase domain. We show further that Tyr877 phosphorylation is mediated by Src and that it is necessary for the enhanced kinase activity of ErbB2. Finally, computer modeling of the kinase domain suggests a phosphorylation-dependent reorientation of the activation loop, denoting the importance of Tyr877 phosphorylation for ErbB2 activity. These findings suggest that Hsp90 binding to ErbB2 participates in regulation of kinase activity as well as kinase stability.